2022
DOI: 10.1136/bmjsem-2021-001214
|View full text |Cite
|
Sign up to set email alerts
|

Throwing in the deep end: athletes, coaches and support staff experiences, perceptions and beliefs of upper limb injuries and training load in elite women’s water polo

Abstract: To understand elite athlete, coach and support staff experiences, perceptions and beliefs in women’s water polo with managing upper limb injuries and monitoring training loads. Inductive qualitative design. Twenty athletes, coaches and support staff were purposively recruited and participated in semistructured interviews. Participants either had experienced an upper limb injury or had experience managing athletes with upper limb injuries. Interviews were conducted in-person or virtually, audio-recorded, deiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A previous water polo observational study suggested that the ability to prescribe training at both an individual and team level may be key to optimizing training volume, intensity, and density progressions (8). Improved information would potentially optimize return-to-play processes and inform individual rehabilitation programs based on previous training history (42). Currently, this capability does not exist and is curtailing optimizing training prescription and, in doing so, potentially leading to nonoptimal systematic and graduated training progression (40).…”
Section: Discussionmentioning
confidence: 99%
“…A previous water polo observational study suggested that the ability to prescribe training at both an individual and team level may be key to optimizing training volume, intensity, and density progressions (8). Improved information would potentially optimize return-to-play processes and inform individual rehabilitation programs based on previous training history (42). Currently, this capability does not exist and is curtailing optimizing training prescription and, in doing so, potentially leading to nonoptimal systematic and graduated training progression (40).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the coaches, having the statistical analysis and the advice of specialized health professionals of different specialties, can structure individualized training programs for each athlete. In this way, harmonious cooperation is created between the members of the scientific team, the athletes, and the coaches, which improves the daily life and the competitive performance of the young athletes [ 20 ]. Furthermore, when these measurements are repeated during the season, a more detailed profile of the athlete is built, and coaches are given the opportunity to know the status of their athletes at any time.…”
Section: Discussionmentioning
confidence: 99%
“…64,65,68,72 However, these quantified subjective and objective training load metrics tend to be regularly combined with a form of non-quantified subjective information such as athlete feedback, athletecoach interaction, or coach perception. 40,53,60,[64][65][66]68,70,72 "On occasion the self-reporting of wellness and internal loads can be at odds with the external loads provided. i.e., there have been times when the data is saying back off a bit but the athlete is saying no I'm good let's go" 68 -Local, national or international level swim coach or support staff Performance monitoring, which is the monitoring of metrics directly related to the performance outcome during training or competition such as speed, distance, power, or points scored, is considered by some coaches as one of the most important forms of athlete monitoring.…”
Section: Athlete Monitoring Methodsmentioning
confidence: 99%